Research on the redesign of precision tools and their manufacturing process based on selective laser melting (SLM). Issue 1 (18th January 2016) - Wang, Di; Song, Changhui; Yang, Yongqiang; Liu, Ruicheng; Ye, Ziheng; Xiao, Dongming; Liu, Yang
Abstract : Purpose: – This paper aims to verify that additive manufacturing technology could be used for the redesign and rapid manufacturing of tools and determine whether the mechanical performance of such tools can satisfy the practical operating requirements. Design/methodology/approach: – A special key was selected as the research object in this paper. The special key was innovatively redesigned and manufactured directly using selective laser melting (SLM). The function and critical geometries of the special key were first analysed, which was followed by discussions on the geometrical constraints in the manufacturing of typical geometrical features using SLM technology. Next, the special key was redesigned based on the SLM geometrical constraints and the functional requirements. Finally, the key was manufactured using SLM, and the mechanical performance characteristics of the key were determined. Findings: – The minimal geometrical feature was 0.2 mm when manufacturing thin walls using SLM. The reliable building angle of an overhanging surface was 40°. The top surface quality of the part could be greatly improved through laser surface re-melting. The volume of the redesigned special key based on the SLM process was only one-third to one-fourth of the original key. The mechanical properties, such as tensile strength and micro-hardness, of the samples manufactured using SLM were able to reach the practical operating requirements. Originality/value: – It is completely feasible to redesign and manufacture precision tools based on the innovative approach of SLM. The advantages of the redesigned tools includes the lack of design restrictions that hinder traditional manufacturing methods, material savings, ability to produce tools that cannot be easily copied and rapid production speed for a small number of tools.